1998
DOI: 10.1192/apt.4.4.211
|View full text |Cite
|
Sign up to set email alerts
|

Second World War veterans with chronic post-traumatic stress disorder

Abstract: The present case study describes a typically complex clinical presentation of chronic post-traumatic stress disorder (PTSD) suffered by a Second World War veteran and advises on multi-disciplinary out-patient management extending to acute hospital care. Limited symptomatic impact of psychological and psychopharmacological therapies is discussed, and related to patient reports of satisfaction with therapeutic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The most convincing evidence for delayed-onset PTSD was from three motor vehicle accident victims who were under continuing medical care for their physical injuries prior to onset, making detection of symptoms in the posttrauma period more likely if present (12,13). In the six studies describing elderly war veterans with very long intervals to first onset, 18 of the 22 cases were corroborated by someone else, in most cases a relative and usually the spouse (15,19,20). Given the age of the veterans, this does not rule out the possibility of episodes in the early months or years posttrauma that might have gone undisclosed or been forgotten, a limitation noted in two studies (20,15).…”
Section: Case Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The most convincing evidence for delayed-onset PTSD was from three motor vehicle accident victims who were under continuing medical care for their physical injuries prior to onset, making detection of symptoms in the posttrauma period more likely if present (12,13). In the six studies describing elderly war veterans with very long intervals to first onset, 18 of the 22 cases were corroborated by someone else, in most cases a relative and usually the spouse (15,19,20). Given the age of the veterans, this does not rule out the possibility of episodes in the early months or years posttrauma that might have gone undisclosed or been forgotten, a limitation noted in two studies (20,15).…”
Section: Case Studiesmentioning
confidence: 98%
“…Of the 10 studies that met inclusion criteria for review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), seven reported delayed-onset PTSD in relation to war experiences (14)(15)(16)(17)(19)(20)(21) and three in relation to motor vehicle accidents (12,13,18). Four of the studies used DSM-IV diagnostic criteria, which include clinically significant distress or impairment in social, occupational, or important areas of functioning (criterion F).…”
Section: Case Studiesmentioning
confidence: 99%
“…The core symptoms of PTSD are intrusive re-experiencing of traumatic events, hyperarousal in reaction to minor stimuli and avoidance of trauma-related triggers. In this paper we describe the phenomenon of intrusive reexperiencing, of which the post-traumatic nightmare (PTNM) is an impressive manifestation that causes considerable distress (Mellman et al, 1995;Schreuder, 1996;Ørner & de Loos, 1998;Schreuder et al, 1998).…”
Section: This Paper Joinsmentioning
confidence: 99%